2013
DOI: 10.1038/pr.2013.15
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate–mediated blood pressure control in preterm fetal sheep under normal and hypoxic–ischemic conditions

Abstract: Background:The understanding of hypoxemia-induced changes in baroreflex function is limited and may be studied in a fetal sheep experiment before, during, and after standardized hypoxic conditions. Methods: Preterm fetal lambs were instrumented at 102 d gestation (term: 146 d). At 106 d, intrauterine hypoxia-ischemia was induced by 25 min of umbilical cord occlusion (UCO). Baroreflex-related fluctuations were calculated at 30-min intervals during the first week after UCO by transfer function (crossspectral) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…We therefore assessed the baroreceptor reflex as an indicator for function of the brain stem. This is clinically of importance since the baroreflex is a vital part of the cardiovascular auto regulatory system in preterm infants, which secures adequate perfusion of the preterm brain [ 22 ]. The cerebrovascular system is still immature in prematurity, making the preterm brain extremely vulnerable to fluctuations in blood pressure caused by HI (or other adverse events such as infection) [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We therefore assessed the baroreceptor reflex as an indicator for function of the brain stem. This is clinically of importance since the baroreflex is a vital part of the cardiovascular auto regulatory system in preterm infants, which secures adequate perfusion of the preterm brain [ 22 ]. The cerebrovascular system is still immature in prematurity, making the preterm brain extremely vulnerable to fluctuations in blood pressure caused by HI (or other adverse events such as infection) [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cerebrovascular system is still immature in prematurity, making the preterm brain extremely vulnerable to fluctuations in blood pressure caused by HI (or other adverse events such as infection) [ 30 ]. Previously, we demonstrated that global HI disturbed normal development of the baroreflex, which resulted in impairment of heart rate-mediated blood pressure control [ 22 ]. The fact that MAPC treatment at 1 h and 4 days improved baroreflex sensitivity indicated that the therapeutic effects reach as far as the highly conserved central brain functions in the brainstem and supports the concept of MAPC-induced protection against grey matter injury in the hypoxic-ischemic preterm brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To quantify baroreflex‐mediated heart rate response (baroreceptor reflex sensitivity), the ratio between the standard deviation of the mean heart rate variability and that of the mean systolic blood pressure was calculated, as reported previously [24, 25].…”
Section: Methodsmentioning
confidence: 99%
“…These parameters have been indicated and validated in studies previously analyzing various heart diseases. [42][43][44] After completion of the studies, the mice were allowed to recover for 24 h after which they were euthanized and the hearts were dissected quantitatively and weighed. Heart weights are reported as absolute weight and as normalized for body surface area as calculated using Meeh's formula.…”
Section: Ecgmentioning
confidence: 99%